Mix design and physical and mechanical properties of pervious concretes - Ximenes, J. (2022)
Fast-growing climate changes are known to have diverse impacts worldwide, even in large cities. Pervious concrete can be a successful safety solution for increasingly frequent heavy rains and floods. This study focuses on achieving an optimized pervious concrete within the scope of international standards by analyzing concretes made with different W/C ratios and vibration times. The results of the study show the strong influence of parameters such as porosity, permeability, and mechanical strengths. Concrete with 0.35 W/C ratio and 40 seconds vibration time was selected for its adequate physical and mechanical properties.